Influence of fly-ash on the engineering characteristics of stabilised clay soil. (2021) - Deepak, M.S.; Rohini, S.; Harini, B.S.; Ananthi, G. Beulah Gnana
Abstract: Soil must be able to withstand the load and transfer it to ground within the range of allowable deformations, for which it must possess good physical and geotechnical properties. Clay soils become more adhesive once when it becomes wet and whereas if it is dry it is characterised by surface cracks. To overcome these circumstances in soil, it should be treated and stabilized in best way. In this study, the influence of two different kinds of Fly-Ashes namely, Class-F Fly-Ash and Class-C Fly-Ash along with the inclusion of lime in the improvisation of stability characteristics of clayey soil. Experiments were conducted to determine the Atterberg limits, Standard Proctor Compaction values and Un-Confined Compression strength of various soil samples with different mix ratios to evaluate influence of Fly-Ash in the stabilisation process. Addressing to the fact that Fly-Ash does not possess any plastic property, the Clay-Fly-Ash mixes show a decrease in Plasticity Index (P.I.) value with increase in the Fly-Ash content. Fly-Ash addition in the clay soil mix that contains lime decreases the plasticity of soil, and also escalates the workability. The workability is increased by modifications in its particle size and collision behaviour. It is concluded that, the addition of lime and Fly-Ash influenced to acquire to stronger and stiffer soil matrix by reducing the inter particle spacing. Based on the experimental study results, the addition of C-Class Fly-Ash was found to be more effective than F-Class Fly-Ash when supplemented along with lime.